NMR investigation of the equilibrium partitioning of a water‐soluble bile salt protein carrier to phospholipid vesicles. Issue 10 (13th August 2013) - Ceccon, Alberto; D'Onofrio, Mariapina; Zanzoni, Serena; Longo, Dario Livio; Aime, Silvio; Molinari, Henriette; Assfalg, Michael
ABSTRACT Membrane binding by cytosolic fatty acid binding proteins (FABP) appears to constitute a key step of intracellular lipid trafficking. We applied NMR spectroscopy to study the partitioning of a water‐soluble bile acid binding protein (BABP), belonging to the FABP family, between its free and lipid‐vesicle‐bound states. As the lipid‐bound protein was NMR‐invisible, the signals of the free biomolecule were analyzed to obtain quantitative information on binding affinity and steady‐state kinetics. The data indicated a reversible interaction of BABP with anionic vesicles occurring in a very slow exchange regime on the NMR time scale. The approximate binding epitope was demonstrated from results on BABP samples in which different positively charged lysine residues were mutated to neutral alanines. H/D exchange measurements indicated a higher exposure to solvent for the core amino acid residues in the liposome‐bound state. Finally, the BABP‐liposome interaction was also investigated for the first time through an MRI‐chemical exchange saturation transfer experiment that has potential applications not only in the field of biology, but also in biomedicine, bioanalytical chemistry, and nanotechnology. Proteins 2013; 81:1776–1791. © 2013 Wiley Periodicals, Inc.